2018
DOI: 10.1007/s10557-018-6815-9
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor and the Prevention of Microvascular Complications in Diabetes Patients with Lower Extremity Arterial Disease; Rationale and Design of the Hema-Kinesis Trial

Abstract: Hema-kinesis will evaluate whether ticagrelor monotherapy or ticagrelor combined with aspirin as compared with aspirin monotherapy can reduce blood viscosity-dependent blood flow in the feet of type 2 diabetes patients with LEAD. Eligible study participants will be randomized into a three-arm double-dummy crossover trial design. All subjects will have baseline blood viscosity measurements and determinations of microvascular flow using laser Doppler flowmetry. If the results of Hema-kinesis are positive, ticagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Details of the trial design have been reported previously. Hema-kinesis is a randomized, double-blind, double-dummy, crossover trial design that compares treatment with aspirin 81 mg/ticagrelor placebo, aspirin 81 mg/ticagrelor 90 mg twice daily and aspirin placebo/ticagrelor 90 mg twice daily on high-shear (300 s −1 ) and low-shear (5 s −1 ) blood viscosity ( NCT02325466 ) [22]. The inclusion and exclusion criteria are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the trial design have been reported previously. Hema-kinesis is a randomized, double-blind, double-dummy, crossover trial design that compares treatment with aspirin 81 mg/ticagrelor placebo, aspirin 81 mg/ticagrelor 90 mg twice daily and aspirin placebo/ticagrelor 90 mg twice daily on high-shear (300 s −1 ) and low-shear (5 s −1 ) blood viscosity ( NCT02325466 ) [22]. The inclusion and exclusion criteria are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Ticagrelor and matching placebo, as well as aspirin and matching placebo, were compounded then over-encapsulated to maintain double-blind conditions. Stability and antimicrobial quality assurance tests were performed prior to and post over-encapsulation [22]. The Clinical Materials Services Unit of the University of Rochester Medical Center (Rochester, NY) prepared study medication kits.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study revealed that in patients with acute ischemic stroke treated with clopidogrel, a good CYP2C19 genotype for clopidogrel metabolism was associated with a 31% decrease in the relative risk of recurrent stroke [10]. Informative studies on pharmacological therapies for reducing BV are limited [11,12]. One study showed that in patients with subclinical carotid or femoral atherosclerosis, clopidogrel reduces the mean low-shear BV by 18% after 3 weeks of treatment [12].…”
Section: Introductionmentioning
confidence: 99%